Report on RiceAdvice Lite validation trial (RAL VAT) conducted in irrigated and rainfed lowlands in framework of AICCRA - Ahouanton, Kokou; Dossou-Yovo, E.R (2024)
This report outlines the RiceAdvice Lite validation conducted during the 2024 wet season in Mali under the AICCRA project. The validation aimed to evaluate fertilizer guidelines from RiceAdvice Lite, compare actual yields using these guidelines versus farmers' practices, and assess fertilizer management on rice fields. A total of 96 farmers, including 39 females, participated in the trial, with 100 rice fields used for the validation. The trial included setting up plots with RiceAdvice Lite recommendations and collecting data on fertilizer use, sowing dates, and yields. Technicians and farmers were trained on the RiceAdvice Lite app and protocol. Despite some drought conditions in Sikasso, the trial proceeded smoothly. The data analysis showed yield increase by 45% due to the implementation of RiceAdvice Lite recommendations.